Ustilago nuda تأثير نقع حبوب الشعير بتراكيز مختلفة من حامض أستيل سالسليك (الأسبرين) على اإلصابة بمرض التفحم السائب - حمد, عبد الحسين (University of Thi-Qar Journal of Science, 2010)
Four concentrates (0,1,2,3) mg Acetyl Salicylic Acid are used to know the effect on Barleyloose Smut disease . Results shown that Acetyl Salicylic Acid effect on percent infection , thepercent reach( 0%) in ( 3) mg concentration . The Correlation Coefficients are significant at0.01 level between the levels of concentration and percent of infection